Optical mode-controlled topological edge state in waveguide lattice - Zhou Changyu; Xie Zhenwei; Lei Ting; Zhang Yao; Chen Qinmiao; Yuan Xiaocong (Nanophotonics, 2024)
Topological edge state (TES) has emerged as a significant research focus in photonics due to its unique property of unidirectional transmission. This feature provides immunity to certain structural disorders or perturbations, greatly improving the robustness of photonic systems and enabling various applications such as optical isolation and topological lasers. Nevertheless, most of current researches focus on the fixed generated TES with no means to control, leaving untapped potential for manipulating the TES through specific methods. In this work, we propose a topological Su–Schriffer–Heeger (SSH) waveguides-lattice scheme that enables the controllable TES without changing the topological phase of the system. Light is selectively localized at the edges of the SSH waveguide lattice, which is determined by the special waveguide modes. Eventually, achieving an effective mode splitter. To validate our proposal, we further demonstrate such mode-controlled TES with a fabricated on-chip device in experiment. The experimentally tested results confirm a successful separation of the waveguide modes with the mode extinction ratio of approximately 10 dB in each channel near the wavelength of 1550 nm. This scheme presents a promising approach for manipulating the TES in photonic systems, thereby facilitating the design of optical controllable topological photonic devices.